Motivasi Masyarakat Usia di Atas 45 Tahun dalam Menerima Vaksinasi COVID-19 - Septiyani, Ayu Nabiha; Azinar, Muhammad (Indonesian Journal of Public Health and Nutrition, 2023)
Background: The COVID-19 pandemic has caused the government to set a policy for COVID-19 vaccination to reduce the number of COVID-19 spikes. In Magelang City, especially in South Jurangombo Village, there were 11 out of 25 people unwilling to take the COVID-19 vaccination. Therefore, this study aimed to analyze the factors related to the motivation of people over 45 years old to access COVID-19 vaccination services in Jurangombo Selatan Village. Methods: This study used an observational analytic research with a cross sectional research design. The sample required in this research was 100 respondens with non-probability sampling technique. The instrument used in this study was a questionnaire sheet in the form of questions for each research variable. The data analysis used in this study was Chi Square statistical test. Results: The results showed knowledge (p-value = 0.035), attitude (p-value = 0.006), education (p-value = 0.001), disease history (p-value = 0.015), health care recommendations (p-value = 0.002), perception vaccine safety (p-value=0.003), perception of vaccine effectiveness (p-value=0.0001), perception of vaccine side effects (p-value=0.002), other people’s behavior (p-value=0.033) were related to vaccination motivation. Meanwhile, the perception of the severity of COVID-19 (p-value=0.456) was not related to the motivation to vaccinate. Conclusion: Factors related to vaccination willingness were knowledge, attitude, education, medical history, recommendations for health care providers, perceptions of vaccine safety, perceptions of vaccine side effects, perceptions of vaccine effectiveness, and the behavior of others.